Gender Effect on Students’ Academic Performance in Block-laying and Concrete Works in Technical Colleges in Edo State - Aigboduwa, Stephen Ayemwenre; Izuhunwa, Osagiede; Odugbemi, Wasiu Olayinka (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study examined the gender effect on students’ academic performance in block-laying and concrete works in technical colleges in Edo State. One research question was raised to guide the study and one hypothesis formulated and tested at 0.05 level of significance. No sampling technique used, due to the manageable size of the population. The research instrument was subjected to test-retest reliability test technique. The reliability coefficient was calculated using Cronbach-Alpha coefficient which yielded reliability value of 0.64. The data collected were analyzed using Mean and Standard Deviation and t-test. Mean and standard deviation were used to analyze the research question and t-test was used to test the hypothesis at 0.05 level of significance. The results of the study showed that although the male students had slightly better performance compared to the female students, it was not significant. Based on the findings of this study, it was recommended that Parents are encouraged to provide the right education they can afford for their children irrespective of gender. Also, there should be a deliberate Federal Government policy to encourage absorbance of female students into further studies in block-laying and concrete works.
Keywords: Education; gender; students’ performance